Exercise-Based Interventions and C-Reactive Protein in Overweight and Obese Youths: A Meta-Analysis of Randomized Controlled Trials - Garcia-Hermoso, A (Nature Publishing Group, 2016)
Background:One of the most commonly measured markers of inflammation in clinical settings is C-reactive protein (CRP). The purpose of this meta-analysis was to examine the evidence for the effectiveness of physical exercise interventions on modifying the levels of serum CRP in children and adolescents with excess of weight.Methods:Two independent reviewers assessed articles from seven databases. Studies were limited to physical exercise interventions in children and adolescents diagnosed as overweight or obese, and including a comparison control group. Weighted mean difference (WMD) was calculated using random-effects model and potential moderators were explored (i.e., weight status, ages, duration of study, frequency of exercise per week, and duration of session). The heterogeneity of the studies was estimated using Cochran s Q-statistic and I 2.Results:Nine randomized controlled trials met the inclusion criteria (n = 427 youths). Overall, results suggest a nonsignificant trend toward a reduction CRP levels (WMD = -0.72 mg/l; 95% confidence interval: -1.52 to 0.08; P = 0.077). Also, there were not significant moderators of exercise effects on CRP.Conclusion:These results suggest that exercise programs in children and adolescents not mitigate the inflammatory effects of excess weight, although there was a trend toward reduction. © 2016 International Pediatric Research Foundation, Inc.